1990
DOI: 10.1159/000288373
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Depressed Mood in the Psychiatric Patient

Abstract: The relationship between depressed mood and alexithymia, measured by the Toronto Alexithymia Scale (TAS) was investigated in a group of psychiatric inpatients (n = 81) and outpatients (n = 97). In both cohorts correlations between the TAS and obsessoid personality style were significant when controlled for mood. The obsessoid style, measured by the Hysteroid-Obsessoid Scale was the most powerful predictor of alexithymia in regression models for each cohort. These data suggest that alexithymia is not a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 18 publications
3
28
0
3
Order By: Relevance
“…Earlier studies have shown [42]that low life satisfaction is associated with such factors as depression and poor social support. Similar findings have been reported by Wise et al [12]in a study of heterogeneous psychiatric patients. Nevertheless, the cross-sectional design used in this study does not enable the impact of life satisfaction to be more specifically evaluated.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Earlier studies have shown [42]that low life satisfaction is associated with such factors as depression and poor social support. Similar findings have been reported by Wise et al [12]in a study of heterogeneous psychiatric patients. Nevertheless, the cross-sectional design used in this study does not enable the impact of life satisfaction to be more specifically evaluated.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, the prevalence of alexithymia in psychiatric patients has varied between 11 and 48% [7, 12, 17, 20, 28, 36]. A higher prevalence (48%) has been noted in substance abusers [4], whereas in the general population alexithymia seems to be less common, usually under 20% [13, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: AnaCatarinaNS@gmail.com ligado a este grupo de transtornos, tornou-se rapidamente evidente que a alexitimia estava presente num largo espectro de perturbações, tais como: perturbações alimentares (e.g., Bourke, Taylor, Parker, & Bagby, 1992;Merino, Godas, & Pombo, 2002;Petterson, 2004), abuso e dependência de substâncias (e.g., Gomez, Eizaguirre, & Aresti, 1997;Haviland, Hendryx, Shaw, & Henry 1994;Speranza et al, 2004;Uzun, 2003), perturbações de ansiedade e depressão (e.g., Wise, Mann, & Hill, 1990;Zeitlan & McNally, 1993) e perturbação de pós-stress traumático (e.g., Hyer, Woods, & Boudewyns, 1991;Krystal, 1979). A investigação sugere ainda uma relação entre alexitimia e perturbações da personalidade, verificando-se uma associação com as perturbações anti-sociais, narcísicas e borderline (Sifneos, 1973;Taylor, 2000;Zlotnick, Mattia, & Zimmerman, 2001).…”
Section: Alexitimiaunclassified
“…Apesar dos vários estudos que demonstram a existência de uma elevada prevalência de pacientes com funcionamento alexitímico na população clínica -superior a 32.7% em pacientes psiquiátricos de ambulatório, cerca de 47.3% em pacientes internados (Todarello, Taylor, Parker, & Fanelli, 1995;Wise et al, 1990) e acima dos 60% em pacientes com pós stress traumático (Zeitlan & McNally, 1993) -muitas vezes esta dimensão não é tida em conta na intervenção psicoterapêutica. Ogrodniczuk (2007) chamou recentemente a atenção para a questão de que, ao longo dos anos, a investigação sobre este constructo se centrou mais na etiologia, descurando a investigação relativa a formas de intervir em contexto terapêutico.…”
Section: Alexitimia E Processo Terapêuticounclassified